Navigating the "delicate relationship between empathy and critical distance": Youth literacies, social justice and arts-based inquiry. Issue 3 (5th December 2016) - Simon, Rob; Evis, Sarah; Walkland, Ty; Kalan, Amir; Baer, Pamela
Abstract : Purpose: This paper features artwork and artists' statements by middle school students who participated in a research collaboration that involved co-authoring critical literacy curriculum for Art Spiegelman's graphic novel Maus: A Survivors Tale (1986) with teacher candidates from the University of Toronto. Design/methodology/approach: Youth explored personal and social justice issues through writing and artwork produced in response to Maus . In the process, they navigated what historian Dominick LaCapra (1998) has referred to as the "delicate relationship between empathy and critical distance" (pp. 4-5), between closely identifying with the agonizing experiences Spiegelman documents and using their inquiries to cultivate more critical positionalities and assume activist stances on historical and contemporary social justice issues. Findings: As they describe in their brief statements included alongside their artwork, creating these projects allowed youth to bear witness to a terrible moment in human history and to envision how they can make a difference in their own communities. Originality/value: This work suggests how the arts can be mobilized in critical literacy as a vehicle to interrogate difficult historical moments and multifaceted identity issues.